The development of a patient reported outcome measure and imaging modalities in the evaluation of haemorrhoidal disease - Parsons, Caron Saeko (2012)
With the advent of DGHAL and PPH, treatments that purport to work by disrupting the arterial supply of haemorrhoids, there has been resurgence in interest in the vascular theory of pathogenesis of haemorrhoids. Despite uncertainty surrounding recurrence and complication rates there has been significant uptake of the new surgical approach due to decreased post-operative pain. However this has not been matched by discussion or evaluation of how haemorrhoidal disease and successful outcome should be evaluated.